Educar en Positivo - Gonzalo, Ignacio (REICE. Revista Iberoamericana sobre Calidad, Eficacia y Cambio en Educación, 2016)
El autor pretende rescatar algunas de las ideas ofrecidas en el Libro “Educar en positivo para un mundo en cambio” de Mercedes Muñoz Repiso y de su dedicatoria manuscrita, con la finalidad de beneficial sobre todo a quienes no hayan tenido ocasión de leerlo. Descriptores: Cambio educativo, pedagogía, fines de la educación. To Educate in Positive The article elaborates a brief route through the history of teaching Compared Education in Spain, and marks respect to all the people who as Mercedes Muñoz-Repiso have contributed to the development of this subject. The authors finalize with some reflections on the future of the Comparative Education after its first review of the study plans. Keywords: Educative change, pedagogy, aims of the education.